Autism Spectrum Disorder and Narcolepsy: A Possible Connection That Deserves to Be Investigated - Posar, Annio; Visconti, Paola; Blunda, Vincenza; Pizza, Fabio; Plazzi, Giuseppe (Frontiers in Psychiatry, 2020)
Narcolepsy in childhood-adolescence is characterized by a high occurrence of psychiatric comorbidities. The most frequent psychiatric disorders reported in these patients are attention deficit/hyperactivity disorder, depression, anxiety disorder, and schizophrenia. However, narcolepsy can be associated also with introversion, sorrowfulness, feelings of inferiority, impaired affectivity modulation, emotional lability, irritability, aggressiveness, and poor attention, that have been pooled by some authors under a definition of “narcoleptic personality”. Some aspects of this “narcoleptic personality”, and in particular introversion, impaired affectivity modulation, irritability, and poor attention, partially overlap with the clinical features of the individuals with autism spectrum disorder. Till now, in literature the number of cases affected by both narcolepsy and autism spectrum disorder (seven patients) has been clearly too small to demonstrate the presence of a pathogenetic link between these two conditions, but this association has not yet been adequately investigated, despite the presence of several points in common. The finding of a non-random association between narcolepsy and autism spectrum disorder could boost the study of possible etiopathogenetic mechanisms shared between these two apparently so distant disorders. Basing on the literature data summarized in this paper, in the diagnostic work-up of a child with narcolepsy it is essential to evaluate also the social-communicative behavior using standardized tools in order to detect the real recurrence of clinical features suggesting an autism spectrum disorder. At the same time, it appears necessary to screen in the individuals with autism spectrum disorder for the possible presence of evoking symptoms of narcolepsy.